KREATIVITAS PRODUK GELAR KARYA MAHASISWA PROGRAM STUDI PKK KONSENTRASI TATA BUSANA UNNES ANGKATAN 2010 - Hidayah, Afifatul (Department of Home Economics, Faculty of Engineering, Universitas Negeri Semarang, 2014)
Mata Kuliah Gelar Karya membutuhkan kreativitas dari mahasiswa agar produk yang dihasilkan variatif serta inovatif. Tujuan penelitian ini adalah untuk mengetahui kreativitasÂ menciptakan produk busana pada Gelar Karya.Metode penelitian ini adalah penelitian kualitatif, dengan fokus penelitian kreativitas produk Gelar Karya prodi PKK Konsentrasi Tata Busana Unnes angkatan 2010. Pengumpulan data dilakukan dengan metode observasi, wawancara dan dokumentasi, untuk pendukung keabsahan data menggunakan triangulasi sumber.Hasil dari penelitian ini menunjukkan bahwa kreativitas produk Gelar Karya mahasiswa Prodi PKK Konsentrasi Tata Busana Unnes angkatan 2010 sudah cukup baik. Dalam proses kreativitas, tahap persiapan kurang maksimal sehingga menyebabkan proses selanjutnya kurang optimal. ProdukÂ Gelar Karya dengan kombinasi-kombinasi kreativitas mahasiswa sesuai dengan tema yang ditentukan sehingga hasil karya busana bersifat original dan variatif serta inovatif. Saran yang dapat peneliti ajukan berdasarkan hasil penelitian dalam Manajemen waktu mahasiswa Gelar Karya sebaiknya lebih ditata lagi agar seimbang antara tugas kepanitiaan dengan tugas Mata Kuliah Gelar Karya Busana sehingga kreativitas produk yang dihasilkan lebih maksimal lagi. Courses Degree Work requires creativity of students so that the resulting products are varied and innovative. The purpose of this research is to know the creativity to create a fashion product in the title of the paper. Method of research is qualitative research, with a focus on creativity research product Title ByProdi PKK Concentration Of force Unnes 2010 Fashion. Data collection is done by the method of observation, interview and documentation, for supporting the validity of the data using triangulation of sources. The results of this research suggest that Title Student Paper Product Creativity Prodi PKK Concentration Of force Unnes Fashion 2010 is already good enough. In the process of creativity, insufficient preparation phase so that the next process causes less than optimal. The product Works with a combination of Degree-a combination of the creativity of students in accordance with the specified theme work clothing is so original and varied and innovative. Researchers can submit suggestions based on research results in students ' time management title of the paper should be more balanced between order again laid out the task of the Committee with the task of Degree Courses Of Fashion so that the resulting product creativity more maximum again. Courses Degree Work requires creativity of students so that the resulting products are varied and innovative. The purpose of this research is to know the creativity to create a fashion product in the title of the paper. Method of research is qualitative research, with a focus on creativity research product Title ByProdi PKK Concentration Of force Unnes 2010 Fashion. Data collection is done by the method of observation, interview and documentation, for supporting the validity of the data using triangulation of sources. The results of this research suggest that Title Student Paper Product Creativity Prodi PKK Concentration Of force Unnes Fashion 2010 is already good enough. In the process of creativity, insufficient preparation phase so that the next process causes less than optimal. The product Works with a combination of Degree-a combination of the creativity of students in accordance with the specified theme work clothing is so original and varied and innovative. Researchers can submit suggestions based on research results in students ' time management title of the paper should be more balanced between order again laid out the task of the Committee with the task of Degree Courses Of Fashion so that the resulting product creativity more maximum again.